Bone Marrow Edema in Osteoporotic Vertebral Compression Fractures after Percutaneous Vertebroplasty and Relation with Clinical Outcome - Voormolen, M.H.J.; van Rooij, W.J.; van der Graaf, Y.; Lohle, P.N.M.; Lampmann, L.E.H.; Juttmann, J.R.; Sluzewski, M. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Little is known about the evolution of bone marrow edema (BME) in osteoporotic vertebral compression fractures (VCF) after percutaneous vertebroplasty (PV) or about its relation with relief of pain. In this study, we prospectively assessed changes in BME with MR imaging at 3, 6, and 12 months after PV and related changes in BME with pain evolution and analgesic use over time.METHODS: BME percentage was assessed in 64 patients after PV of 89 VCF with serial MR imaging follow-up at 3, 6, and 12 months. Pain was assessed before PV and at every follow-up interval by visual analog scale for pain and type of analgesic used. Relation between changes in BME and pain evolution was assessed in a subgroup of 31 patients with a single treated VCF and neither new VCF at follow-up nor pain at another untreated level.RESULTS: BME gradually decreased over time. At 1 year after PV, 29% of treated VCF still demonstrated BME. Once BME disappeared, it did not return. Pain relief was most striking the first 3 months after PV and remained constant thereafter. There was no relation between relief of pain and extent, presence, or absence of BME after PV.CONCLUSION: A gradual decrease of BME in osteoporotic VCF treated with PV is apparent during 12 months of MR imaging follow-up. Decrease of BME is unrelated to relief of pain.